Spatial analysis and climatic factors related to dengue in a small municipality of São Paulo, Brazil - Peres Neto, João; Praddo da Fonseca, Emílio; Rosário de Sousa, Maria da Luz; Tennant, Marc (Journal of Health & Biological Sciences, 2017)
Objective: to analyze the relationship of climatic variables, temperature and rainfall, - with dengue, in addition to identifying possible areas of greater spatial concentration of confirmed dengue cases. Methods: This is an ecological study with secondary data in the city of Ubirajara / SP. The confirmed cases of Dengue, assumed as an outcome, were obtained from the Aging and Notification Information System (SINAN) of the Ministry of Health; while the climatic data were used as independent variables and temperature and precipitation were provided by IPMet - Center of Meteorology of Bauru / SP, from 2007 to 2015. Pearson’s correlation (r) was used for statistical analyzes. The addresses were geocoded and related to the digital cartoFigureic base of the municipality through the software QGIS and elaborated the thematic map through the kernel intensity estimator. Results: 187 cases of dengue were reported in the study period, with 119 cases (63.7%) occurring in 2015 with an incidence coefficient of 25.39 cases per 1,000 inhabitants. Mean annual temperature correlated positively with dengue and (r) (Pearson) cases = 0.6889, p = 0.0401 (α = Type I error) and β = 0.6652 (Type II error). The Kernel map identified four areas of greatest concentration for dengue transmission. Conclusions: The relationship between temperature increase and dengue cases requires adequate responses from the institutions, with continuous monitoring of trends, construction of predictive models for the formulation of plans by using spatial analysis in the identification of the priority areas for actions that will be performed.